(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The article discusses the current trends in using internet technologies in teaching English as a foreign language, categorizing the versatile platforms, tools and technologies, and highlighting the importance of each category of tools. The author also stresses the future prospects in using such technologies for teaching foreign languages, specifically English in this context.